Nursing Care for Patients with Diabetes Mellitus with Bed Rest Interventions Against the Incidence of Decubitus Ulcers in Abdul Manap Hospital Jambi - Sulistiawan, Andika; Intan Syafika (Program Studi Keperawatan Universitas Jambi, 2022)
Decubitus is a wound caused by excessive external pressure, generally occurring in patients suffering from chronic diseases who often lie in bed for a long time. Another factor that causes decubitus is the presence of a long history of Diabetes Mellitus. The intervention carried out for decubitus is the provision of bed rest. Switching beds every 2 hours can improve blood circulation and improve metabolic regulation to restore the physiology of vital organs and accelerate wound healing. The purpose of this study was to provide Nursing Care for Diabetes Mellitus Patients with Bed Rest Interventions against the Incidence of Decubitus Ulcers in the Interne Room of H. Abdul Manap Hospital, Jambi City. Method: a case study was used. Results: The analysis showed that there was a diagnosis of impaired skin integrity with the intervention of giving bed rest for 3 days, the results showed that after bed rest there was a decrease in the Braden scale on the first day of intervention with a scale of 12 (high risk of pressure sores) after the third day of intervention with a scale of 13 (moderate risk of pressure sores). The conclusion of the study is that shifting beds can reduce and prevent decubitus.